2013
DOI: 10.3390/ijfs1040168
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Positive Expected Returns in the UK Fixed Odds Betting Market: An Analysis of the Fink Tank Predictions

Abstract: Abstract:We report striking evidence of semi-strong inefficiency in the UK fixed-odds football betting market using a reputable newspaper tipster which offers probabilities of match outcomes rather than simple result indicators. Betting on the Fink Tank probabilities of home wins across 10 bookmakers, when there are positive expected returns, would have generated positive returns in each of the seasons from 2006-07 to 2011-12 for a variety of different betting strategies. These returns could have been enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…This is consistent with other attempts in the literature to compare statistical models and bookmakers as football match forecasters (e.g. Boshnakov et al., 2017; Buraimo et al., 2013), though in these previous cases, the comparisons used betting strategies and returns on investment, and focused on match results rather than scorelines.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This is consistent with other attempts in the literature to compare statistical models and bookmakers as football match forecasters (e.g. Boshnakov et al., 2017; Buraimo et al., 2013), though in these previous cases, the comparisons used betting strategies and returns on investment, and focused on match results rather than scorelines.…”
Section: Resultssupporting
confidence: 88%
“…Similarly, Buraimo et al. (2013) have shown that using straightforward betting strategies for football match results, whenever positive returns were expected based on the University of Warwick's “Fink Tank” statistical model's probability forecasts, which were published in a British newspaper, would have generated positive expected returns for each season of the English Premier League between 2006/07 and 2011/12.…”
Section: Related Literaturementioning
confidence: 97%